ANALISIS PEMBENTUK PORTOFOLIO OPTIMAL DENGAN PENDEKATAN CAPITAL ASSET PRICING MODEL DAN FAMA-FRENCH FIVE FACTOR MODEL PADA JAKARTA ISLAMIC INDEX - Andyni Rahmadhani Putri (2022)
This study aims to determine the combination of stocks formed from the optimal portfolio in the Capital Asset Pricing Model and the Fama-French Five Factor Model in 2018-2021. The sampling method is through the full sampling method. The data analysis technique used in this study is analysis using optimal portofolio. The results showed that (1) The combination of stock portfolios using the Capital Asset Pricing Model model is CTRA, SMGR, SMRA, and WSKT. (2) Combination of stock portfolios using the Fama-French Five Factor Model model contained in the composition of B/H, B/C, and B/R, namely TLKM, ICBP, UNTR, KLBF, and INDF. (3) The results of this study show that the Fama-French Five Factor Model model is more accurate than the Capital Asset Pricing Model in determining investments.